Teachers’ Social and Emotional Competencies and Their Role in Occupational Well-Being - Mirta Mornar (Psychological Topics, 2024)
The teaching profession is characterised by high levels of stress and numerous emotional challenges, especially in the early stages of a career. Previous research suggests that teachers’ social and emotional competencies (SEC) are related to their occupational well-being as they influence the way they cope with everyday emotional challenges at work. This points to the role of SEC as potential psychological resources that can mitigate negative outcomes such as burnout and leaving the profession among teachers in the early stages of their career. However, research in this area is still scarce and it is unclear how certain SEC are related to different aspects of occupational well-being and commitment to the teaching profession. The aim of this paper is to review conceptual frameworks of SEC and existing research in the field, discuss the role they play in education and compare them with related constructs in the domain of individual differences. Furthermore, it will provide an overview of research on teachers’ occupational well-being and examine the relevance of teachers’ SEC for outcomes such as burnout, work engagement, and job satisfaction. The paper will conclude by examining methodological aspects of SEC assessment and review challenges and directions for future research.